Utilization of and Barriers to HIV and MCH Services among Community ART Group Members and Their Families in Tete, Mozambique. (17th July 2013) - Geelhoed, Diederike; Decroo, Tom; Dezembro, Sergio; Matias, Humberto; Lessitala, Faustino; Muzila, Fausto; Brumana, Luisa; Capobianco, Emanuele
Abstract : Mozambique continues to face many challenges in HIV and maternal and child health care (MCH). Community-based antiretroviral treatment groups (CAG) enhance retention to care among members, but whether such benefits extend to their families and to MCH remains unclear. In 2011 we studied utilization of HIV and MCH services among CAG members and their family aggregates in Changara, Mozambique, through a mixed-method assessment. We systematically revised all patient-held health cards from CAG members and their non-CAG family aggregate members and conducted semistructured group discussions on MCH topics. Quantitative data were analysed in EPI-Info. Qualitative data were manually thematically analysed. Information was retrieved from 1, 624 persons, of which 420 were CAG members (26%). Good compliance with HIV treatment among CAG members was shared with non-CAG HIV-positive family members on treatment, but many family aggregate members remained without testing, and, when HIV positive, without HIV treatment. No positive effects from the CAG model were found for MCH service utilization. Barriers for utilization mentioned centred on insufficient knowledge, limited community-health facility collaboration, and structural health system limitations. CAG members were open to include MCH in their groups, offering the possibility to extend patient involvement to other health needs. We recommend that lessons learnt from HIV-based activism, patient involvement, and community participation are applied to broader SRH services, including MCH care.